The Future of Acid Inhibition - Guido NJ Tytgat (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
There are many unmet needs with current gastric acid suppression with proton pump inhibitors (PPIs). Recommended prescription of one standard morning dose for all patients and for all medical conditions must be scientifically inappropriate and far from individualized personal medicine. For several diseases, especially gastroesophageal reflux disease and Barrett esophagus, more intense, more prolonged diurnal acid suppression is indicated. Especially inhibition of nocturnal acid secretion with our current delayed-release PPIs turns out to be difficult. This overview summarizes the actual attempts to improve the control of acid secretion, which is necessary to adapt the degree of acid inhibition to the individual patient needs. To be discussed are: immediately release PPIs, extended PPI formulations, PPIs with a much longer half-life, potassium competitive acid blockers, gastrin antagonists, etc. Future studies have to proof that those novel drug approaches indeed contribute to reduce the unmet needs. Keywords: acid secretion, PPI, nocturnal acid secretion